Resource allocation algorithm for intelligent reflecting surface-aided SWIPT networks - Wei SUN; Qingyang SONG; Lei GUO (Tongxin xuebao)
In order to achieve the efficient interconnection of everything, under the limitations of terminal devices’ batteries and network coverage, the intelligent reflecting surface (IRS) technology was introduced to build a new IRS-aided simultaneous wireless information and power transfer (SWIPT) network.To further improve the total throughput of the network, a resource allocation (RA) scheme aiming at sum-rate maximization was proposed.Considering that the constraints of the maximum transmit power of a base station, the minimum energy requirement of each device and the phase shifts on an IRS, a joint transmit beamforming, power splitting (PS) ratio and phase shift optimization problem was formulated.Due to the non-convex problem and coupled variables, a block coordinate descent (BCD)-based algorithm was proposed.Then, the joint transmit beam forming design, PS ratio optimization and phase shift design were solved by using the successive convex approximation (SCA) and Riemannian manifold methods, respectively.Simulation results show that the proposed RA scheme performs better than the existing RA schemes in terms of sum-rate.